Pengembangan Rancangan Aplikasi Hear Talk Me untuk di Gunakan Penyandang Tunarungu Berbasis Sistem Operasi Android - Rakhmadi Rahman; Muhammad Aril; Ananda Nabila Putri (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
With all respect and gratitude, we express our gratitude to the presence of Allah SWT who has bestowed His grace and grace, so that we can complete a paper entitled